2019
DOI: 10.1371/journal.pone.0211700
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of moderate vs. high iso-inertial loads on power, velocity, work and hamstring contractile function after flywheel resistance exercise

Abstract: Flywheel iso-inertial training has been shown to positively affect muscular strength and sports performance (e.g. agility). However, implementing such eccentrically-biased training during a microcycle needs to be carefully planned due to its purported effects on the neuromuscular system that can last for hours/days post-exercise. This study aimed at using tensiomyography to verify the effects of different inertias during the hip extension exercise on the contractile function of biceps femoris and semitendinosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 43 publications
2
41
2
Order By: Relevance
“…In our case all groups showed a decrease in Tc after the eccentric overload exercise. Also, previous studies using eccentric overload exercises showed increased Tc values at 24 h [ 34 ], which are related, together with Dm changes, to muscle damage in both the neuronal and structural systems [ 35 ]. Therefore, the similar correlations shown in the treated leg in the case of MT and PT have great relevance when considering studies such as that of Dupuy et al (2018) [ 36 ], who compared the effects of MT with other therapies including compression garments, cold water immersion, electrostimulation and cold water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case all groups showed a decrease in Tc after the eccentric overload exercise. Also, previous studies using eccentric overload exercises showed increased Tc values at 24 h [ 34 ], which are related, together with Dm changes, to muscle damage in both the neuronal and structural systems [ 35 ]. Therefore, the similar correlations shown in the treated leg in the case of MT and PT have great relevance when considering studies such as that of Dupuy et al (2018) [ 36 ], who compared the effects of MT with other therapies including compression garments, cold water immersion, electrostimulation and cold water.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown significant increases in Dm values at 24 h after eccentric overload, but no change after 48 or 72 h [ 34 ]. These findings show that the load factor plays a crucial role in muscle changes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…8,30,31 Although different intensities of EOL squats have previously resulted in no meaningful difference in jump potentiation, 16 they may differentially activate musculature of Page 5 of 10 the lower limbs in individuals. 18 Recording the power output during EOL exercise may help to clarify this.…”
Section: Discussionmentioning
confidence: 99%
“…However, this often leads to “wasted repetitions” (i.e., repetitions needed to get the flywheel up to the desired velocity), training to failure, and poor training load management. Previous research has suggested that lower inertial training loads may produce greater adaptations for peak power, while moderate to high inertial loads may provide greater ECC overload [ 112 , 115 ]. However, as previously noted, larger inertial loads may increase the length of the ECC phase of the movement, which may modify the ECC overload stimulus [ 109 ].…”
Section: Eccentric Training Methodsmentioning
confidence: 99%